Profitability analysis of Aloe vera (L.) production in selected areas of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
Medicinal plants serve as important therapeutic agents as well as valuable raw materials for manufacturing numerous traditional and modern medicines. Aloe vera is a top ranked medicinal plant in Bangladesh. The objective of this study is to investigate the costs, returns and profitability of Aloe vera medicinal plant. The data were collected from the selected farmers of Bogura and Natore districts in Bangladesh during 2018. The total sample size is 123. The study applies the profitability analysis, break-even points and margin of safety percentage techniques. Surveyed farms are found at ranged from 0.01 to 0.41 hectares. Average cost of production per hectare is found at Tk. 876468.80, of which Tk. 647156.40 for operational cost and Tk. 229312.40 for fixed costs accounting for 73.84% and 26.16% of the total cost, respectively. The average yield of Aloe vera is stood at 41487.62 kg per hectare which is sold to two different markets: contract markets and local market. The mean price is estimated at Tk. 32.42 per kg in study area. The gross margin and net margin per hectare are found to be Tk. 698068.02 and Tk. 468755.61, respectively. The breakeven analysis showed that in the case of yield and price, the margin of safety percentage of Aloe vera is -53.48. It is also found at 42.01, 67.15 and 34.85 for variable cost, fixed cost and total cost of Aloe vera production. Therefore, the study noted that the Aloe vera medicinal plant production is profitable in the study area. Farmers have a great opportunity to allocate more land to Aloe vera production, which will make them more profit. Break-even analysis of Aloe vera production resists a large drop of yield and price before incurring a loss, which gives the farmers a comfortable margin of safety and a risk bearing ability.Res. Agric., Livest. Fish.7(1): 75-81, April 2020